Tableau de la géographie littéraire - Brosseau, Marc (Sp@tialités, 2022)
The trajectory of literary geography accompanies that of the multiple branches and trends of human geography. Although marginal for a long time, resorting to literature is now a common practice in geography. The accuracy of the description of rural landscapes in the realist novel, the form of the city in the modernist novel, the urban imagination in science fiction and detective fiction are some of the many topics explored in literary works. Considered as a whole, the mass of works published over the past fifty years is impressive, and sufficiently rich and diversified that it would not be excessive to speak of a relatively autonomous sub-discipline whose developments proceed from the mobilization of theoretical frameworks, methodological approaches, or even hitherto unexplored themes. This book reconstructs the evolution of this flourishing field of research and identifies its most promising contemporary orientations. It shows that literary geography constitutes a kind of crossroads where conceptions of the discipline, methodological issues, critical prerogatives, and intellectual traditions intersect and sometimes collide.